2013
DOI: 10.5194/bg-10-7525-2013
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of photosynthetic carbon assimilation efficiency by phytoplankton in the future coastal ocean

Abstract: Abstract. A mesocosm experiment was conducted to evaluate the influence of photosynthetic performance on the energetic balance of coastal phytoplankton, in relation to community production and autotrophic phytoplankton biomass in future coastal oceans. Natural phytoplankton assemblages were incubated in field mesocosms under ambient condition (control: ca. 400 μatm CO2 and ambient temperature), and two sets of potential future ocean conditions (acidification: ca. 900 μatm CO2 and ambient temperature; greenhous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 43 publications
(54 reference statements)
5
25
0
1
Order By: Relevance
“…There was a significant increase in the ETR max under OA (Table 3), which indicates an increase in 315 photosynthetic capacity. Previous studies on picoeukaryotes have reported variable results with studies displaying no change or an increase in ETR max in response to OA (Brading et al, 2011;Fu et al, 2007;Kim et al, 2013). In this study, I k increased in concert with ETR max with increasing pCO 2 (Table 3).…”
Section: Picoeukaryotes Benefit From Ocean Acidification Irrespectivesupporting
confidence: 42%
“…There was a significant increase in the ETR max under OA (Table 3), which indicates an increase in 315 photosynthetic capacity. Previous studies on picoeukaryotes have reported variable results with studies displaying no change or an increase in ETR max in response to OA (Brading et al, 2011;Fu et al, 2007;Kim et al, 2013). In this study, I k increased in concert with ETR max with increasing pCO 2 (Table 3).…”
Section: Picoeukaryotes Benefit From Ocean Acidification Irrespectivesupporting
confidence: 42%
“…During this experiment, in which nutrient were added, a shift from particulate to dissolved organic carbon was measured at high CO 2 level (Kim et al, 2011) as well as an increase in light utilization efficiency that was not reflected on the gross community production (Kim et al, 2013). Under negligible grazing pressure (top-down control), high CO 2 level has the potential to increase growth and primary production of phytoplankton by enhancing the inorganic carbon assimilation efficiency (Kim et al, 2013) for this community dominated by diatoms and dinoflagellates in the post-bloom period (Table 3). …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The most significant response was, however, exerted by elevated CO 2 , probably due to the close relationship between esterase activity and photosynthetic metabolism (Dorsey et al 1989, Sobrino et al 2005b). Downregulation of the photosynthetic apparatus under high CO 2 conditions has been proposed as an important metabolic process, but the physiological mechanisms and its consequences for the biogeochemical cycles are only starting to be understood (Raven 1991, Sobrino et al 2008, Beardall et al 2009, Hopkinson et al 2010, Kim et al 2013). It will be considered with more detail later in the discussion.…”
Section: Metabolic Activity and Cell Damagementioning
confidence: 99%
“…The response has been related to a downregulation of the photosynthetic machinery by high CO 2 levels, which reduces the incorporation and synthesis of new metabolic components, thus reducing intra cellular pools, and therefore reducing compounds involved in repair mechanisms (Sobrino et al 2008(Sobrino et al , 2009). However, some contrasting re sponses have also been observed (Sobrino et al 2005a, García-Gómez et al 2014 and further information about the molecular mechanisms and the consequences of downregulation for cell metabolism is still needed (Raven 1991, Hopkinson et al 2010, Kim et al 2013.…”
Section: Introductionmentioning
confidence: 99%